Formation Mechanism via a Heterocoagulation Approach of FePt Nanoparticles Using the Modified Polyol Process - Beck, Watson; Souza, Caio G. S.; Silva, Tiago L.; Jafelicci, Miguel [UNESP]; Varanda, Laudemir C. (Amer Chemical Soc, 2011)
Herein, we report a new approach of an FePt nanoparticle formation mechanism studying the evolution of particle size and composition during the synthesis using the modified polyol process. One of the factors limiting their application in ultra-high-density magnetic storage media is the particle-to-particle composition, which affects the A1-to-L1(0) transformation as well as their magnetic properties. There are many controversies in the literature concerning the mechanism of the FePt formation, which seems to be the key to understanding the compositional chemical distribution. Our results convincingly show that, initially, Pt nuclei are formed due to reduction of Pt(acac)(2) by the diol, followed by heterocoagulation of Fe cluster species formed from Fe(acac)(3) thermal decomposition onto the Pt nuclei. Complete reduction of heterocoagulated iron species seems to involve a CO-spillover process, in which the Pt nuclei surface acts as a heterogeneous catalyst, leading to the improvement of the single-particle composition control and allowing a much narrower compositional distribution. Our results show significant decreases in the particle-to-particle composition range, improving the A1-to-L1(0) phase transformation and, consequently, the magnetic properties when compared with other reported methods.